Variabmty and Genetic Control of Some Inorganic Elements and Pigments in Leaves of Prosopis cineraria (L.) MacBride - Manga, V K; Sen, David N (Annals of Arid Zone, 2016)
Variability for inorganic elements and leaf pigments was studied in forty accessions of Prosopis cineraria (L.) MacBride collected from different districts of Rajasthan, Gujarat and Haryana. Significant differences were observed for chlorophyll a, chlorophyll b. crude protein, sodium, potassium, calcium and phosphorus. Sodium (23.00) and carotenoids (22.91) had high values of phenotypic coefficients of variation, Genotypic coefficient of variation was highest for carotenoids (20.34). Estimates of heritability in broad sense were highest for potassium (0.88), closely followed by crude protein (0.81), sodium (0.80) and chlorophyll a (0.80). Genetic advance expressed as per cent of mean was highest (37.26%) for carotenoids followed by sodium, potassium and calcium. Chlorophyll a. b, and total chlorophyll had moderate values of genetic advance. Accessions showing high protein content, low to moderate sodium and high phosphorus were, NIC-1936, NIC-1937, NIC-1840, NIC-196 J, NIC-I920, NIC-13555 and NIC-13570.